2019
DOI: 10.3390/ijerph16132427
|View full text |Cite
|
Sign up to set email alerts
|

Human Error: The Impact of Job Insecurity on Attention-Related Cognitive Errors and Error Detection

Abstract: (1) Background: Work-related stress is a major contributor to human error. One significant workplace stressor is job insecurity, which has been linked to an increased likelihood of experiencing burnout. This, in turn, might affect human error, specifically attention-related cognitive errors (ARCES) and the ability to detect errors. ARCES can be costly for organizations and pose a safety risk. Equally detrimental effects can be caused by failure to detect errors before they can cause harm. (2) Methods: We gathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 63 publications
0
12
0
1
Order By: Relevance
“…There are several reasons that can cause human errors in a firm, such as work-related stress, stress from job insecurity, wage, or location, etc. (Roll et al, 2019). It would be wise to understand the managers' and owner's opinions regarding the employee error rate and its effect on the firm's performance.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…There are several reasons that can cause human errors in a firm, such as work-related stress, stress from job insecurity, wage, or location, etc. (Roll et al, 2019). It would be wise to understand the managers' and owner's opinions regarding the employee error rate and its effect on the firm's performance.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In the assessment of cognitive functions in the workplace, no specific neuropsychological batteries were found to be used consistently and uniformly for this purpose. on the other hand, tests and scales were found that are used to measure cognitive functions in different work environments such as aviation (Asmayawati & Nixon, 2020), military activities (Frings, 2011;Irgens-Hansen et al, 2015;Smith et al, 2019, Bell, Virden, lewis & Cassidy, 2015, conduction (Horrey, lesch & Garabet, 2009; Cheng, Ting, Liu & Ba, 2015;De Oliveira et al, 2020;Chen, Chou, Su & Wen, 2019, Di Nocera et al, 2018, Adrian, Postal, Moessinger, Rascle & Charles, 2011Elfer-ing, Grebner & Haller, 2012), construction (Brossoit et al, 2019), service sector (Roll, Siu, li & de Witte, 2019;Elfering, Grebner & de Tribolet-Hardy, 2013), industrial operators and services (Kodappully, Srinivasan & Srinivasan, 2016;Muller et al, 2012) and other activities (Buodo, Patron, Benvenuti & Palomba, 2018;Askaripoor et al, 2019;Petitta, Probst, Ghezzi & Barbaranelli, 2019;Huang, Menozzi & Favey, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The findings of this review show the limited number of investigations that relate the establishment of neuropsychological profiles associated with occupational accidents. Unified evaluations are evidenced and few establish a comprehensive profile as an object of study, some cognitive functions most evaluated in reported investigations were attention and memory (Buodo et al, 2018;Asmayawati & Nixon, 2020;Chen et al, 2019;Brossoit et al, 2019;Roll et al, 2019;Petitta et al, 2019;Askaripoor et al, 2019;Di Nocera et al, 2018;Kodappully et al, 2016;Irgens et al, 2015;Bell et al, 2015;Elfering et al, 2012;2013;Muller et al, 2012;Horrey et al, 2009) were evaluated to a lesser extent as cognitive flexibility and processing speed (Frings, 2011;Bell et al, 2015;Muller et al, 2012;Adrian et al, 2011). It is important to point out that this review seeks to gather the greatest evidence that reflects the state of research and knowledge gaps in the study of the performance of cognitive functions in occupational accidents, since accidents in the workplace affect many spheres of work-business and personal life, implying a high financial and social cost (Feng et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, tests and scales were found that are used to measure cognitive functions in different work environments such as aviation (Asmayawati & Nixon, 2020), military activities (Frings, 2011;Irgens-hansen et al, 2015;Smith et al, 2019, Bell, virden, Lewis & Cassidy, 2015, conduction (horrey, Lesch & garabet, 2009; Source: Authors. Cheng, Ting, Liu & Ba, 2015;De Oliveira et al, 2020;Chen, Chou, Su & Wen, 2019, Di Nocera et al, 2018, Adrian, Postal, Moessinger, Rascle & Charles, 2011Elfer-ing, grebner & haller, 2012), construction (Brossoit et al, 2019), service sector (Roll, Siu, Li & De Witte, 2019;Elfering, grebner & De Tribolet-hardy, 2013), industrial operators and services (kodappully, Srinivasan & Srinivasan, 2016;Muller et al, 2012) and other activities (Buodo, Patron, Benvenuti & Palomba, 2018;Askaripoor et al, 2019;Petitta, Probst, ghezzi & Barbaranelli, 2019;huang, Menozzi & Favey, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Source: Authors. Chen et al, 2019;Brossoit et al, 2019;Roll et al, 2019;Petitta et al, 2019;Askaripoor et al, 2019;Di Nocera et al, 2018;kodappully et al, 2016;Irgens et al, 2015;Bell et al, 2015;Elfering et al, 2012;2013;Muller et al, 2012;horrey et al, 2009) were evaluated to a lesser extent as cognitive flexibility and processing speed (Frings, 2011;Bell et al, 2015;Muller et al, 2012;Adrian et al, 2011). It is important to point out that this review seeks to gather the greatest evidence that reflects the state of research and knowledge gaps in the study of the performance of cognitive functions in occupational accidents, since accidents in the workplace affect many spheres of work-business and personal life, implying a high financial and social cost (Feng et al, 2015).…”
Section: Horreylesch and Garabet 2009mentioning
confidence: 99%